Ethanolic extract of Morinda citrifolia improves gut microbiota, intestinal morphology, and performance without adverse effects on hematological profiles in broiler chickens - Paredes-López, Daniel Marco; Robles-Huaynate, Rizal; Perales-Camacho, Rosa Amelia; Alania-Santiago, Cindy Vanessa; Aldava-Pardave, Uriel (Frontiers in Veterinary Science, 2026)
Over the last six decades, the extensive use of antibiotics as growth promoters in animal nutrition has contributed to antimicrobial resistance and ultimately poses a risk to public and environmental health. Therefore, there is a growing interest in alternative strategies, such as plant extracts and essential oils, to address this issue. The aim of this study was to evaluate the effect of Morinda citrifolia leaf ethanolic extract (MCEE) on the intestinal health and performance of broiler chickens. A total of 360 Cobb 500 broilers were randomly distributed into groups C1, C2, S1, S2, and S3, with six replicates of 12 chickens each. C1 was fed the base diet (BD), and C2 was fed BD + 50 ppm zinc bacitracin (ZB). S1, S2, and S3 were supplemented with MCEE in daily doses of 5.62, 11.0, and 16.3 mg/kg BW, respectively, from 1 to 21 days of age. Hematological profiles and gut histology were assessed at 7, 14, and 21 days of age, while the abundance of microbiota in the ileum was measured at 21 and 28 days of age. Performance indices, including weight gain, feed intake, and feed conversion rate, were evaluated at 7, 21, and 33 days of age. Data were analyzed using a general factorial arrangement. The abundance of Escherichia coli and Staphylococcus aureus log (CFU/g) decreased in the three supplemented groups by 21 days of age, and these levels were maintained until 28 days of age. Additionally, in the three supplemented groups, the abundance of Lactobacillus sp. decreased by 21 days of age; however, it was re-established by 28 days of age. Villus height and crypt depth increased with age in the S2 group by 21 days of age. Performance indices improved during the fattening phase overall in chickens in group S2. In conclusion, a daily dose of 11.0 mg/kg BW MCEE in the diet improved performance indices by modulating gut microbiota and histology at 21 days in broiler chickens.